Evaluation of the association of bruxism, psychosocial and sociodemographic factors in preschoolers - Monalisa Cesarino GOMES (Brazilian Oral Research, 2018)
Abstract The aim of the present study was to evaluate factors associated with sleep bruxism in five-year-old preschool children. A preschool-based cross-sectional study was conducted with 761 pairs of children and their parents/caregivers. Sleep bruxism was diagnosed using a questionnaire administered to the parents/caregivers, who also answered questionnaires addressing sociodemographic data and parent’s/caregiver’s sense of coherence. Clinical oral evaluations of the children to determine dental caries, traumatic dental injuries, malocclusion and tooth wear were performed by two researchers who had undergone a training exercise (interexaminer Kappa: 0.70 to 0.91; intraexaminer Kappa: 0.81 to 1.00). Descriptive analysis and logistic regression for complex samples were carried out (α = 5%). The prevalence of sleep bruxism among the preschool children was 26.9%. The multivariate analysis revealed that bruxism was associated with poor sleep quality (OR = 2.93; 95 CI: 1.52–5.65) and tooth wear (OR = 2.34; 95%CI: 1.39–3.96). In the present study, sleep bruxism among preschool children was associated with tooth wear and poor sleep quality of the child. In contrast, psychosocial aspects (sense of coherence) were not associated with sleep bruxism.